Scientific network agreement "Polish Scientific Network - research and development works for the promotion of sports law" - selected organizational and legal issues - Borek, Dominik; Raniszewski, Szymon; Bugajska, Małgorzata (Quality in Sport, 2023)
The article concerns the cooperation agreement between scientific units in the field of sports law. The Network, not having legal personality, uses the legal personality of its members. The network is not a civil law partnership agreement. The coordinator of the network agreement is the John Paul II Catholic University of Lublin in Lublin. The members of the network remained fully independent in their non-target activities. The study used the dogmatic-exegetical research method, which required an analysis of detailed legal regulations in this area. The article presents the personal views of the authors and cannot be interpreted as the position of any authority, entity or institution.